Identifying the Professional Characteristics of Researchers in Educational Fields at Sudanese Universities from the Views of Educational Experts - Ahmed Mohammed Al-Hassan Shennan; Zeinab Mohammed Ibrahim Kassab (University of Science and Technology, Yemen, 2016)
The present study aims at identifying the characteristics, research abilities and skills that the researcher in the educational fields should possess and their role in enriching research outcomes. A second aim was whether these characteristics are met by Sudanese University staff embarked on educational research. The study adopted the descriptive correlational and induction methods. The university staff members who conduct research in the educational fields constitute the population of the present study. A systematic stratified sample of 48 lecturers from 12 universities was selected and a Likert type-based questionnaire was applied. Three main domains that help in doing educational research were identified. The questionnaire is composed of these main domains; the intellectual characteristic (11 items), the psycho-social characteristics (12 items), and research skills (15 items). Results of the pilot study showed that the questionnaire achieved good reliability, validity and internal consistency coefficients and hence was suitable for the purpose of this study. The SPSS program was used for data analysis. Findings showed significant positive correlation between the intellectual characteristic and years of experience (0.03) and the professional level of members of staff (0.001).The psycho-social characteristics were not significantly correlated with years of experience while they are positively correlated with the professional level of members of staff (0.001). Although 66.6% of the subjects were found to command the necessary research skills, yet they were not significantly correlated with years of experience. These findings are discussed in the light of relevant literature. More specifically, from the professional and ethical stance, Sudanese universities are expected to pay more attention to capacity building in educational scientific research since it is the cornerstone of human development.